Zlati standard - sero-submukozni (ekstramukozni) šiv intestinalne anastomoze - Vračko, Jože (Endoskopska revija, 2006)
The paper describes the advantages of serosubmucosal (extramucosal) sutures for intestinal anastomosis, presents the new insights into histology and physiology of wound healing, and stresses the significance of the basal membrane biological potential in the healing of intestinal anastomosis.
Keywords: Anastomoza kirurška; Surgical Wound Dehiscence; Suture Techniques; Bazalna membrana; Enterostomija; Basement Membrane; Enterostomy; Kirurška rana, dehiscenca; Anastomosis, Surgical; Šivanje, tehnika; kirurško zdravljenje; rane; anastomoza; šivanje